The Poverty Level in Yogyakarta City: Examining the Influencing Factors with a Multidimensional Approach - Nursamsiyah; Ulung Pribadi; Titin Purwaningsih (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Poverty is a complex issue that requires an in-depth understanding of the various factors influencing it. This study aims to analyze the poverty level in Yogyakarta City using a multidimensional approach, as well as identify the factors contributing to this condition. The study employs a quantitative method, with data collected through an empirical survey using structured questionnaires. The respondents of this study are the beneficiaries of the Kartu Maju Sejahtera (Prosperous Advance Card) in Yogyakarta City, Special Region of Yogyakarta. The collected data were analyzed using Smart PLS4 software, with hypothesis testing on variables such as public policy, asset ownership, health, income, and education. The results show that public policy does not have a significant impact on poverty levels. On the other hand, asset ownership, health, income, and education have a significant influence on poverty levels and play an important role. Higher education is strongly correlated with a reduction in poverty levels, while effective public policies, although important, show limitations in their implementation. Moreover, health has a significant impact, but limited access to healthcare services affects the statistical results. The study concludes that increasing income could be a key solution to reducing poverty. These findings emphasize the importance of a multidimensional approach to understanding poverty, highlighting that non-economic factors such as education, health, and asset ownership also play vital roles in determining the welfare of the community. The study provides implications for policymakers to integrate more holistic strategies in poverty alleviation efforts.